The Influence of the Trump Era on Sustaining Whiteness through Imperialist Reclamation on College Campuses: How Undocumented Students Experience the Normalization of Racist Nativism - Darsella Vigil; Susana M. Muñoz (MDPI AG, 2023)
On 5 September 2017, the Trump administration decided to rescind the Deferred Action for Childhood Action (DACA) policy, impacting over 800,000 recipients, and more colleges and universities witnessed a heightened sense of emboldened racism in college environments. This paper draws from focus groups with undocumented college students on how the Trump era influenced campus climate. We found that imperialist reclamation of whiteness acts targeting undocumented students was commonplace on college campuses, ultimately impacting students' behavior and academic engagement in and outside the classroom.